ANALYSIS OF READINESS OF HEALTH DEPARTMENT IN LABOR GUARANTEE POLICY IN HEALTH OFFICE OF DELI SERDANG DISTRICT 2020 - sinulinggaa, dianaa; Siagian, Nurul; Prima, Armanda; Sembiring, Alprindo (Jurnal Kajian Kesehatan Masyarakat, 2021)
Implementation of the Maternity Assurance Policy (Jampersal) should be supported by the readiness of the Health Office; in Deli Serdang District it was found that there was also one Puskesmas that had computers connected to the internet, health equipment that had not been optimal in supporting midwifery services and inadequate laboratory equipment. This study aims to analyze the readiness of the Deli Serdang District Health Office in the Implementation of Jampersal Policy. This type of research uses a qualitative approach with 5 informants. Data collection is done by observation and in-depth interviews. From the results of the study concluded that the socialization of Jampersal program policies is still lacking. The readiness of the health office in organizing Jampersal from both the number and competence of staff and equipment / consumables is still inadequate, which causes many cases to be referred to hospitals which the health center should still be able to handle. Coordination built by the Health Office, BPJS and puskesmas is also lacking, as can be seen from the misunderstanding of Jampersal participants about participation and the existence of reference cases that cannot be claimed. Deli Serdang district government commitment supports the implementation of a strong Jampersal program, but coordination between local governments and DPRD is still very minimal. It is expected that Deli Serdang District Health Office will improve Jampersal socialization in collaboration with cross-programs / sectors, involve community leaders and accompanied by distributing leaflets, brochures / leaflets, providing training and redistribution to be evenly distributed, immediately fixing equipment, conducting strict supervision of puskesmas regarding the system referral is accompanied by sanctions for those who violate, coordinate with BPJS and puskesmas to improve BPJS membership, improve coordination with the DPR The success of universal coverage in 2019 can be achieved